Implementasi Pemikiran Ekonomi Klasik pada Perekonomian Indonesia di Era Society 5.0 (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2024)
The operation of the economic system in a country depends on the economic system adopted. The idea of the economic system itself has evolved over the centuries. The development of modern economic theory was marked by the emergence of Adam Smith's classical economic theory in 1776. The ideas proposed by Smith were considered revolutionary until they were considered the cause of the first industrial revolution and international trade. Until now, in the era of society 5.0, the concept of this idea is still widely adopted in various countries in the world, including Indonesia.